The Effect of MMS (Metacognitive, Monitoring, Summarizing) Strategy in Improving Students’ Reading Comprehension - Zuhad Ahmad; Widi Sriyanto (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study aimed to find out a significant influence from the use of Metacognitive, Monitoring, and Summarizing (MMS). This research used quantitative with an experimental design using 2 class samples (control class and experimental class) which was randomly selected and each class consisted of 30 students as respondents. Data collection used tests to determine students’ reading skills. The data that has been obtained was analyzed using the t-test in SPSS. Based on the results obtained that the t-count is 0.001 which is lower than